Perancangan dan Implementasi Sistem Keamanan Sepeda Motor Berbasis RFID & SIM GSM - Bambang Suhartono; Dedi Setiawan (Uranus: Jurnal Ilmiah Teknik Elektro, Sains dan Informatika, 2025)
The increasing number of motorcycle thefts in various regions indicates that conventional security systems are not yet fully effective in protecting vehicles, necessitating new technology-based innovations. This study discusses the planning and implementation of a motorcycle security system utilizing Radio-Frequency Identification (RFID) technology as a more responsive and modern solution. The system is designed using a passive RFID tag placed on the motorcycle key, an RFID reader integrated with the motorcycle unit, and an Arduino microcontroller that functions to control the ignition system. With this combination, the motorcycle can only be activated if the appropriate tag is detected, while access attempts using an invalid tag or the loss of the tag will automatically disconnect the ignition system. Test results announced that tag recognition can be done very quickly, in less than a second, so as not to disrupt the user's comfort when starting the vehicle. In addition, this system is able to maintain consistent performance by providing an automatic response that supports advanced security. The implementation of this plan is expected to reduce motorcycle theft by providing an additional layer of security that is more difficult to penetrate than a manual key system. From the user's perspective, this technology remains practical because it does not require complicated procedures in its operation, simply by ensuring the appropriate RFID tag is attached to the motorcycle key. Overall, this research confirms that the application of Arduino microcontroller-based RFID technology can be an alternative, inexpensive, and applicable security system in everyday life. It is hoped that this system will not only improve protection for vehicle owners but also serve as a benchmark for the development of more sophisticated transportation security technologies in the future. Implementation of this system is expected to reduce motorcycle theft and provide a greater sense of security for vehicle owners.